Effect of storage temperature on the stability of the liquid polyvalent antivenom produced in Costa Rica - Rojas Céspedes, Gustavo (1990)
The effect of storage temperature on the stability of the liquid polyvalent (crotaline) antivenom produced at the Instituto Clodomiro Picado, Costa Rica, was studied during a twelve-month period. The following parameters were evaluated: neutralizing potency against lethal activity of Bothrops asper venom; protein and phenol concentrations; pH; turbidity; safety; and sterility. Analyses were performed each month on different samples of a batch, stored .at 4, 23, 30 and 37°C. No significant (P > 0.1) variations occurred in potency, protein and phenol concentrations, pH, sterility or safety, at any of the storage temperatures during the study period. However, visual inspection revealed a moderate increase in turbidity of the samples stored at 23, 30 and 37°C, at nine, four and three months, respectively . Culture of samples excluded the possibility of microbial contamination of the product leading to turbidity. Chromatographic and electrophoretic analyses demonstrated that turbidity was caused by the formation of heterogeneous protein aggregates of high molecular weight . Present results support the conclusion that, although storage temperature (up to 37°C for twelve months) does not alter antivenom potency, it significantly influences the formation of protein aggregates . This phenomenon can be prevented by recommending the storage of antivenom at refrigeration temperature.